The impact of acoustic intensity on solution parameters and decellularization using sonication treatment - Noor Azmi, Azran Azhim; Shafiq, Mohammad; Rasyada, A. Rahman; Furukawa, Katsuko; Ushida, Takashi (American Scientific Publishers, 2015)
A combination method using sonication and chemical treatment to decellularize tissue sample is described. The objective of the study is to determine the acoustic intensity and solution parameters modulating decellularization process. The acoustic intensity distribution of sonication system was first demonstrated by simulation and followed by experimental measurement. The effect of acoustic intensity with solution parameters including dissolved oxygen (DO) concentration, pH, and conductivity was observed using 170 kHz system. From both simulation and experimental results, it is demonstrated that acoustic intensity effects were localised as high cell removal recorded at the center of irradiation. Furthermore, our study demonstrated strong correlation between acoustic intensity with solution parameters. The study indicates positive correlation of DO concentration and pH of SDS detergent with acoustic intensity and negative correlation between conductivity and acoustic intensity. The results further supported by the complete removal of DNA with preservation of extracellular matrix (ECM), collagen and elastin content. In conclusion, the effect of acoustic intensity is localised and influenced decellularization. Our study also indicates strong correlation between acoustic intensity and solution parameters as we suggested the formation of cavitation bubble derived the decellularization process.